Pendekatan Situasional (Jurnal Manajemen Kreatif dan Inovasi, 2023)
This article is made to find out the description of the situational approach study regarding a person's personality that is influenced by conditions or situations that occur in a particular environment. This article is prepared based on a literature study by comparing books, journals and other literature, this writing uses literature study writing. This situational approach explains that a leader must be effective in a variety of organizational settings that relate to the tasks of the organization. There are four styles of situational leadership: S1 is high command-low support, S2 is high command-high support, S3 is low command-high support, and S4 is low command-low support. Situational leadership is related to the level of development of employees or subordinates. The leader's behavior must be able to adjust to the situation and conditions of subordinates who are different from one another and the indicators that influence it are the dimensions of telling, selling, participating, and delegation. The advantage of situational leadership compared to other leadership is that in this situational leadership depends on the level of maturity of the subordinates who will be influenced by the leader.